Superantigen types in Staphylococcus aureus isolated from patients with cystic fibrosis - Bania, J; Dabrowska, A; Rózalska, B; Sadowska, B; Wieckowska-Szakiel, M; Korzekwa, K; Zarczyńska, A; Bystroń, J; Chrzanowska, J; Molenda, J (Folia microbiologica, 2006)
The screening of 17 SAg genes of S. aureus isolated from the sputum of cystic fibrosis (CF) patients revealed that among 47 genetically different strains, 39 (83 %) carried SAg genes. Superantigens forming enterotoxin gene cluster were detected in 20 strains. The 2nd most common superantigen type was selk detected in 13 strains. In 9 strains, selk occurred together with the sea gene. Out of 74 strains recovered from nasal carriers, 56 (75 %) were found to carry SAg genes, 38 carried egc genes, while selk was detected in 5 strains. The predominant SAg types in both investigated S. aureus populations were egc and selk/sea, but selk gene frequency was significantly higher in the CF-derived strains.
Keywords: nosní dutina; Carrier State; Sputum; stafylokokové infekce; Child, Preschool; Bacterial Proteins; Staphylococcus aureus; Genotype; enterotoxiny; Adolescent; Infant; Child; Enterotoxins; Cystic Fibrosis; dítě; přenašečství; sputum; Superantigens; superantigeny; mladiství; antigeny bakteriální; novorozenec; předškolní dítě; pacienti; DNA, Bacterial; Nasal Cavity; DNA bakterií; Patients; lidé; cystická fibróza; Humans; Infant, Newborn; kojenec; bakteriální proteiny; Staphylococcal Infections; genotyp; Antigens, Bacterial